2020
DOI: 10.1186/s40854-020-00195-0
|View full text |Cite
|
Sign up to set email alerts
|

Financial sector development and Investment in selected countries of the Economic Community of West African States: empirical evidence using heterogeneous panel data method

Abstract: This study gives an empirical insight to a theoretical suggestion that financial sector development spur investment. For the case of ECOWAS, we have seen that financial sector development influence on investment is sensitive to the indicator of financial sector development. Empirical insight from the study also revealed that the impact of financial sector development on investment is different across the countries in ECOWAS. This study therefore provide policy recommendations and implications which the countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
(48 reference statements)
2
25
0
Order By: Relevance
“…Energy is the basic building block of all sectors of modern economic growth and is considered a basic factor of production, including capital and labor (Alam et al, 2016;Solarin et al, 2017). However, energy consumption has become a crucial aspect of the economic growth (GDP) of any nation (Azam et al, 2020a;Azam et al, 2020c;Iheonu et al, 2020;Azam et al, 2021a;Azam et al, 2021c). Due to the rapid growth of the global economy, energy consumption is rapidly increasing as a result of globalization and industrialization (Shafique et al, 2020;Shafique et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Energy is the basic building block of all sectors of modern economic growth and is considered a basic factor of production, including capital and labor (Alam et al, 2016;Solarin et al, 2017). However, energy consumption has become a crucial aspect of the economic growth (GDP) of any nation (Azam et al, 2020a;Azam et al, 2020c;Iheonu et al, 2020;Azam et al, 2021a;Azam et al, 2021c). Due to the rapid growth of the global economy, energy consumption is rapidly increasing as a result of globalization and industrialization (Shafique et al, 2020;Shafique et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Annual average of 0.33% and 0.39% with the range of 0.23% to 0.50% and 0.21% to 0.92% recorded in Mexico and Indonesia respectively. While, Turkey was 1.00%on annual average recording 1.00% each rformed below the annual bench mark throughout the period except in 2007 and 2008, and the FSDled to growth in SADC but no statistically significant effect in ECOWAS, as the effect of FSD through institutional development supports a positive complementarity Iheonu et al (2020)research found the impact of financial sector development on domestic investment depends on the measure of financial sector development utilized, as banking intermediation efficiency and broad money supply negatively and significant influence domestic Sarwar et al ( 2020) study revealed that financial development has a positive and significant effect on economic growth of emerging economies. Guru and Yadav ( 2019…”
Section: -003mentioning
confidence: 88%
“…While, Stiglingh, Muzindutsi and Bezuidenhout (2018) succinctly posit that there seems to be a lack of strong financial systems and policies to deliver the required economic results in most developing countries. Iheonu et al (2020) collaborate that development of the financial sector enhances efficient access to financial services and products. Vol 9 Issue 6 D 2.1.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Olanrewaju / International Journal of Finance & Banking Studies, Vol 10 No 1, 2021ISSN: 2147 Review of Empirical Literature Iheonu, Asongu, Odo, and Ojiem (2020) examined the impact of financial system development on investment in Economic Community of West African State (ECOWAS) between the period of 1985 and 2017. By using heterogenous panel data estimation techniques, findings of the study revealed that the effect of financial system development on domestic investment relies on the parameters of financial sector development employed.…”
Section: Introductionmentioning
confidence: 99%